Epidemiological profile of cervical cancer in the State of Piauí (Research, Society and Development, 2021)
This study aims to understand the epidemiological profile of cervical cancer in the State of Piauí to enable the understanding of some aspects related to this pathology, which has a high preventive potential. This is a study with documentary, epidemiological, retrospective, descriptive analysis, with a quantitative approach to data obtained from the Cancer Information System (SISCAN), for the year 2019. The following variables were analyzed: total number of exams, range age, education, preventive period, motivation for the examination and performance of previous cytology. The survey of information showed that 77,841 exams were carried out, the largest amount was concentrated in the age group of 35 to 39 years old and 99.58% (77,514) were motivated by tracking. In this study, 73.98% (57,586) of the women claim to have had a preventive exam before, 15.81% (12,306) did not undergo the test, 8.29% (6,453) do not know and 1.92% (1,494) do not presented information in the form. Regarding education, SISCAN did not provide satisfactory data for analysis. CC screening is a complex action, the number of women affected by this pathology is considered high and significant. The need for knowledge on the subject in question to strengthen and redirect public policies for the control of the CCU is notorious.